Practicing Design Judgement through Intention-Focused Course Curricula - Fernaeus, Ylva; Lundström, Anders (Design and Technology Education: An International Journal, 2015)
This paper elaborates on how design judgement can be practiced in design education, as explored in several iterations of an advanced course in interaction design. The students were probed to address four separate design tasks based on distinct high-level intentions, i.e. to 1) take societal responsibility, 2) to generate profit, 3) to explore a new concept, and 4) to trigger reflection and debate. This structure, we found, served as a valuable tool in our context for bringing important topics to discussion in class and for actively practicing design judgement. We discuss what we see as the main qualities of this approach in relation to more conventional course structures in this area, with a focus directed more towards aspects of methodology, specific interaction techniques, and design principles more generally.